La reestructuración empresarial y la crisis económica peruana en un contexto de globalización económica - Alva Gómez, Juan Amadeo (2002)
In the last years one comes questioning the economic, financial and political effects of the Economic Globalización, in special in the underdeveloped countries had in the first place to the Capitalist prevailing System of the Economic Neoliberalism whose free competition greatly favors to the countries developed by the abysmal differences that exist in relation to the technologies and scientific advances whose activities are more competitive in al! the fields of the economic activity. Indeed these competitive differences have left outside race the incipientes industries of the underdeveloped countries, causing the closing of you make, leisure and misery. The present work, indeed takes care of one of those problems: The Enterprise Reconstruction and the Peruvian Economic Crisis in a Context of Economic Globalización the Methodology that was applied to the work of investigation corresponds to the scheme of lnvestigation established by the Unit of Post Degree of the Faculty of Countable Sciences of the U.N.M.S.M. Being the pro pose Hypotheses for the solution of the created problem the following ones: 1. The Economic Globalización favors fundamentally to the great industries of the countries developed in decline of the incipientes industries of the underdeveloped countries, by the abysmal scientific and technological differences on which it is based his competitive advantages. The propose solution is to establish administrative and economic a policy of reingeniería of the companies, taking advantage of the facilities the Internet and asking for aid to the government in the sense to establish agreements with multinational companies that are committed to enable to the Peruvian personnel with technology of end in contracts of privatization or investment in general. 2. The Peruvian Companies must study what strategic activities have the opportunity to develop as far as possible avoiding to compete with the great companies that very have developed competitive advantages, looking for as far as possible to use the creativity to operate national resources that are profitable as much by their comparative advantages as by their competitive advantages. 3. Internally the State must be a promotional State of the national industry giving laws that truely they protect to this one and not that they are only an instrument of political propaganda as is the case of the Law of Patrimonial Reconstruction. 4. The Peruvian industralist must become qualified mainly in planning strategic to be competitive and to know to handle strategies to confront the changes and crisis that the context presents/displays. 5. The law of Patrimonial Reconstruction has not given results, reason why a new device is due to give that responds to the necessities of reflotamiento of the companies in crisis and not a device that to a great extent favors the Creditors, without concerning the destiny of the company of its workers and the country. The Methodology used for the development the work I frame myself within the following logical methods: The Deductive Method was applied to formally study the conceptual frame referring to the Economic Globalización and Enterprise Reconstruction, as well as all the legal devices that govem the procedure of Patrimonial Reconstruction. The Inductive Method was applied in the work of field for, by an inference process, to confirm and to validate the raised hypotheses the synthetic Analytical Method, allowed me to study the sample type for the study of the phenomenon of the Reconstruction of the Textile Companies, taking as it bases, the particular study of Textile the Consorcio Company of Paci'fico S.A.. For the study of the nature and behavior of the textile companies in crisis use beca me of the Hermenéutico methods, Apodíctico and Diale'ctico, and finally for the objective demonstrations it was used the Statistical Method and the Mathematical Method. In the First Chapter the work begins with the study of Conceptual Marco of the Economic Globalización and its implicancias in the Industrial Sector in Peru. The main Subject is referred the companies of Textile Enterprise Sector 1997. 2001 in processes of Patrimonial Reconstruction and the Conceptualización and application of the law of Enterprise Reconstruction in the occasion of the economic crisis of the companies. The First Chapter talks about to the PROBLEM OF the GLOBALlZACIÓN and the IMPLlCANCIAS IN the ENTERPRISE SECTOR, in where it appears the conceptual frame of the Economic Globalización and its repercussion in the Peruvian industries. The Second Chapter deals with the LEGAL BASE OF the ENTERPRISE RECONSTRUCTION IN PERU, in where Marco appears legal that prevails to the Patrimonial Reconstruction in its different stages from the established systems of Reconstruction from 1992 from 2001. One becomes a special study of the Law of Enterprise Reconstruction, its requirements to enter the system, the procedures of the Patrimonial Reconstruction, the administration of the companies in reconstruction and means of supervision and control. The Third Chapter deals with the Problem of the Recession in Peru and the Companies in Crisis, establishing the causes of the crisis in Peru, being one of the important causes but of the Recession, the caused one by the Economic Globalización. Also in this chapter it deals with the policy of reactivation and the estimate of the companies in crisis. The Fourth Chapter, deals with the project of Patrimonial Reconstruction demanded to the companies in reconstruction according to the Law N° and to the Legislative Decree 845,27146 N° as well as the comparative study of the 10 main textile companies that have entered liquidation the failed salary their process of reconstruction. The Fifth Chapter deals with the Patrimonial Reconstruction in the Textile companies of Lima Metropolitan, taking as study sample the Textile Partnership of Paci'fico S.A., to study all the process of Patrimonial Reconstruction. The Chapter Sixth deals with the Proposal of a Model of Patrimonial Reconstruction like alternative of solution to the created problem. The Work finishes with the respective Conclusions and Recommendations.